Pensions, Price Shocks, and Macroeconomic Stability in Transition Economies : Illustrations From Belarus - Lugaresi, Sergio (IMF Working Papers; Working Paper ;, 1994)
In many countries of the former Soviet Union, pensioners form a large and vulnerable group of the population, with pensions fixed in nominal terms. Attempts to 'protect' this group have included a revaluation of benefits for retirees and the introduction of indexation arrangements based on recent wage and price growth. In this paper, lagged indexation arrangements are shown to have large destabilizing effects that can potentially jeopardize the macroeconomic adjustment effort, particularly as inflation begins to decelerate. Some long-term problems relating to the aging of the population and associated policies are also discussed. Illustrative examples from Belarus are presented.